Portfolio Excess Return Analysis for SRI-KEHATI Index Stocks: Evidence from the Fama-French Three-Factor Model - Mahatir Muhammad (UNKLAB Business School, 2026)
This study addresses the growing investor interest in sustainable investments that consider profitability as well as social, environmental, and governance factors, as reflected in the SRI-KEHATI index on the Indonesia Stock Exchange. Using a quantitative approach, the Fama-French Three Factor Model was applied to estimate the excess returns of stock portfolios listed in the SRI-KEHATI index from 2020 to 2024. The analysis focused on three factors: market risk premium, firm size, and book-to-market ratio. The results show that all three factors have a positive and significant effect on portfolio excess returns. These findings confirm the model’s relevance in the Indonesian market and emphasize the importance of risk and fundamental factors in sustainable investment decisions. The study concludes that the Fama-French Three Factor Model effectively explains excess returns of sustainable stock portfolios and can guide investors in ESG-based investment strategies. Future research should consider additional risk factors, compare the model with newer multifactor models, and expand data scope and analytical methods to better capture market dynamics.